TRANSLATING THEORY INTO PRACTICE: THE GENDER AND DEVELOPMENT TRAINING EVALUATION USING THE KIRKPATRICK’S MODEL (International Conference on Social and Islamic Studies, 2021)
The aim of this study was not only to evaluate the participants’ reactions, learning, behavioral change, and applications of the Gender and Development (GAD) trainings they attended but also to obtain suggestions for the improvement of succeeding trainings. Mixed method was used. Random sampling was applied in selecting the participants. Twenty-eight teachers and staff were involved. Convergence of data and information revealed that GAD trainings brought significant and favorable benefits to the participants. However, the participants were keen on the qualifications of the resource speakers; mediocre attendees; repetition of topics; involvement of other stakeholders; planning and organizing of the trainings. It also revealed that the participants highly regarded the applicability of the concepts presented in the GAD trainings. It was suggested that GAD organizers need to strategize and make thorough planning by looking at every detail of the trainings.